SDM Berbasis Syariah - Amiur Nuruddin (TSAQAFAH, 2010)
Although the market share of Islamic banking is still relatively small, the growth and development of Islamic banking and financial institutions in Indonesia has been quite encouraging. To support the process of socialization and institutionalization of sharia banking working better, the existence of reliable and highly qualified Human Resources is indispensable. This article examines the characteristics of Sharia-based human resources derived from the philosophical framework of Islamic Economics. There are at least four Islamic philosophical basis of economics, namely tauhid (monotheism), justice and balance, freedom, and responsibility. For Islamic financial institutions, both banking and non-banking, as the business institutions based on values and principles of sharia, the qualification and quality of human resources are about an integration between the “knowledge, skill and ability” (KSA) with moral commitment and personal integrity. Some morality aspects referred here are alShiddiq (true, honest), al-amanah (trustworthy, credible), al-Tabligh (communicative) and al-fathanah (intelligent, professional). Moreover, in managing a business, the moral aspects were even as “key success factor”.